AN ANALYSIS OF LEARNERS’ MISTAKES IN USING SIMPLE PAST TENSE IN WRITING CLASS AT MTsN 2 SURAKARTA - sigmawati, ambar herning; sujito, sujito (Smart Education, 2025)
This research aimed to explore the most common errors made by students when applying the simple past tense in their writing, as well as to investigate the factors contributing to these inaccuracies. A qualitative approach was employed, as the researcher sought to analyze learners’ difficulties in using the simple past tense. Based on the findings, it was revealed that these errors primarily stemmed from the students’ lack of comprehension regarding the simple past tense material.